2011
DOI: 10.1167/iovs.10-6755
|View full text |Cite
|
Sign up to set email alerts
|

Visual Functions and Interocular Interactions in Anisometropic Children with and without Amblyopia

Abstract: Interocular interactions are associated with amblyopia, the degree of anisometropia, and amblyopia treatment outcomes, but these associations are visual function dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…In addition, the duration of treatment was longer in the anisometropic group. Lai et al 21 reported that the vision system has greater plasticity in early childhood, which may be related to the difference in our results. Secondly, it has been suggested in the literature that in anisometropia, visual acuity is affected more than contrast sensitivity.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, the duration of treatment was longer in the anisometropic group. Lai et al 21 reported that the vision system has greater plasticity in early childhood, which may be related to the difference in our results. Secondly, it has been suggested in the literature that in anisometropia, visual acuity is affected more than contrast sensitivity.…”
Section: Discussioncontrasting
confidence: 56%
“…Yang & Stevenson (Yang and Stevenson 1999) applied an interocular luminance masking paradigm in normal subjects and found that grating contrast sensitivity of the tested eye was greatly decreased when the mean luminance of a steady uniform field presented to the non-tested eye increased. Lai et al, (2011) found that, with proper optical correction, visual acuity, contrast sensitivity and alignment sensitivity differences of the amblyopic eye between the fully and partially patched fellow eye conditions were significantly higher in anisometropic children with amblyopia, compared to those without amblyopia or normal controls. Freeman & Jolly (1994) found that visual acuity in one eye was not affected by occluding or increasing the luminance in the untested eye uniformly in normal subjects, but presenting a uniform lit field to the untested fellow eye significantly reduced visual acuity in the tested eye in strabismic subjects (Freeman and Jolly 1994).…”
Section: Discussionmentioning
confidence: 85%
“…The study differs from Lai et al (2011) in three aspects: (1) we measured the full contrast sensitivity function with the quick CSF procedure (Lesmes, Lu et al 2010) instead of contrast sensitivity at a single frequency, (2) we compared opaque and translucent patching conditions (0 vs 22.64 cd/m 2 ) while Lai et al compared opaque and dark patching conditions (0 vs 4.62 cd/m 2 ), and (3) in addition to tests under full optical correction, we included a naked eye condition to test the procedure without optical correction. The procedure would be most valuable when optical correction is not available.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…2 The difference in refractive error between two eyes produces abnormal binocular interaction and motivates inhibition of the eye with greater refractive error, resulting in a reduction in its visual acuity. [3][4][5][6] Weakley 7 found that the incidence and depth of amblyopia were associated with the type and magnitude of anisometropia. The risk of amblyopia is high in anisometropia of more than 2.00 DS in myopia, 1.00 DS in hyperopia, and 1.50 DC in astigmatism.…”
Section: Introductionmentioning
confidence: 99%